Antiviral therapy in chronic hepatitis C (G1) in Russia: cost and effectiveness - A. V. Rudakova; D. A. Gusev; A. N. Uskov; Yu. V. Lobzin (Журнал инфектологии, 2015)
Genotype 1 HCV treatment in Russia assume as bitherapy (pegylated interferon – PG plus ribavirin – RBV) as three therapy based on HCV protease inhibitor such as telaprevir (TLV), boceprevir (BCV) or simeprevir (SMV) plus PG/RBV. Medical technologies characterize neither clinical effectiveness, safety profile nor cost-effectiveness so it’s crucial to assess different costs related antiviral regimens. Three therapy costs for naïve patients including TLV, BCV, SMV are higher bitherapy 2,6; 2,5; 3,1 times accordingly. Similar TLV and BCV effectiveness for naïve patients defines TLV or BCV as the preferable 1-st line regimen, depending on regional features of pricing. SMV and TLV efficacy is similar among naïve patients and ralapsers but SMV is affordable for partially responders and non-responders after previous bitherapy. SMV cost is 1,4 times higher vs TLV but SMV has improved tolerability, less drug-drug interactions and shorter course. Insufficient bitherapy effectiveness for G1 HCV (SVR 24 – 39%-55%) is required repeated course of three therapy for half of patient population. The first line regimen based on innovation will improve clinical outcomes for more patients and provide cost saving vs previous bitherapy based on PG/RBV.